Towards a comparison of cohesive reference in English and German: system and text - Kunz, Kerstin; Steiner, Erich (Linguistics and the human sciences, 2010)
The present study is concerned with contrasts in cohesion between English and German, with a special focus on the investigation of cohesive reference. Employing system-based as well as corpus-based methods, we are adding a contrastive to the hitherto dominating monolingual perspectives. Methodologically, we are furthermore attempting to complement the pre-existing system-based accounts with an empirical text-based approach. The paper starts with an overview of different approaches to cohesion, situating and clarifying our own concepts. We then look in more detail at the conceptualizations of cohesive reference and its subcategories before discussing the cohesive resources systemically available in the two language systems for the creation of personal and demonstrative reference. We finally present some preliminary findings from our corpus-linguistic study. These not only test some initial hypotheses derived from the systemic comparison, but also reveal some interesting tendencies with respect to textual frequency and function in the two languages, the registers investigated, and in originals compared to translations. Our study aims at conceptual clarifications, systemic comparisons and some initial textual evidence that may be valuable for basic research as well as language teaching and translator training.
Gesehen am 20.06.2022